The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12978-018-0497-4
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perspectives on antenatal breast expression: a cross-sectional survey

Abstract: BackgroundThe practice of antenatal breast expression (ABE) has been proposed as a strategy to promote successful breastfeeding. Although there has been some focus on the evaluation of the effects of ABE in promotion of breastfeeding, little or no evidence exists on women’s experiences of ABE or opinions on ABE, particularly amongst overweight or obese women.MethodsThis study aimed to explore women’s knowledge, practices and opinions of ABE, and any differences within the overweight and obese subgroups. A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…AME was thought to contribute to breastfeeding success on multiple fronts, most notably in increasing confidence in one's capability to produce milk and express it in the event of postpartum breastfeeding difficulties. Our findings are in line with qualitative and survey research conducted among women in the United Kingdom and Australia, which found that AME was acceptable to women, increased breastfeeding confidence, and contributed to breastfeeding preparation (Brisbane & Giglia, ; Fair et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…AME was thought to contribute to breastfeeding success on multiple fronts, most notably in increasing confidence in one's capability to produce milk and express it in the event of postpartum breastfeeding difficulties. Our findings are in line with qualitative and survey research conducted among women in the United Kingdom and Australia, which found that AME was acceptable to women, increased breastfeeding confidence, and contributed to breastfeeding preparation (Brisbane & Giglia, ; Fair et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Hand expression, rather than an electric breast pump, is the preferred milk removal strategy when milk volumes are small (as in pregnancy), yielding higher milk output (Ohyama, Watabe, & Hayasaka, 2009). Theory and limited research outside the United States suggest that AME may buoy women's breastfeeding confidence, reduce early formula use through "banking" of a back-up supply of breast milk during pregnancy, and hasten the onset of a more copious milk supply post birth through critical-period endocrine modulation (Chapman, Pincombe, & Harris, 2013;Cox, 2006;East, Dolan, & Forster, 2014;Fair, Watson, Gardner, & Soltani, 2018;Forster et al, 2011;Parker, Sullivan, Krueger, & Mueller, 2015). However, women's receptivity to AME, integration of AME into daily life during the third trimester, and perceived benefits and barriers of AME have not previously been evaluated within a sample of U.S. women.…”
mentioning
confidence: 99%
“…Eleven (55.0%) were published within the last 5 years (2015-2019) [21,24,[33][34][35][36][37][38][39][40][41]. Included studies originated from six countries: Australia (n = 7) [13,21,24,[33][34][35][36], New Zealand (n = 1) [42], the United Kingdom (n = 5) [20,39,[43][44][45], Sweden (n = 1) [46], United States (n = 3) [37,38,47], and India (n = 3) [16,40,41]. Three dominant research groups were identified; Forster et al [13,21], Demirci et al [37,38], and Casey et al [35,36], have each published two studies included in our review.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed summary of the studies included in this scoping review is provided in Table 1. This review included one quality improvement study [33], two case studies/series [38,43], four qualitative and/or cross sectional survey studies of the knowledge, attitudes and experiences of women engaging in aBME [34,35,37,39], three observational cohort studies [20,36,46], and ten interventional studies [13, 16, 21, 24, 40-42, 44, 45, 47] including one RCT [21]. Sample sizes of included studies ranged from 1 to 60 (n = 8) [13,34,35,37,38,42,43,47], 80-230 (n = 8) [16,20,24,33,40,41,44,45], and 300-690 (n = 4) [21,36,39,46] participants.…”
Section: Resultsmentioning
confidence: 99%
“…AME refers to extracting colostrum from the breast before birth by hand expressing. Limited studies have been conducted to evaluate the impact of AME intervention on breastfeeding for women with diabetes, and indicate that AME might help to enhance women's breastfeeding con dence, prevent delayed lactogenesis II and improve exclusive breastfeeding rate [17][18][19][20]. However, the impacts of AME to women who are not being with diabetes, particularly in rst-time mothers have not previously been evaluated.…”
Section: Introductionmentioning
confidence: 99%